Factors contributing to collaborative Game-Based Learning (CGBL) effectiveness - Amran, Aryanti; Ab Jalil, Habibah; Muhamad, Mohd Mokhtar; Nasharuddin, Nurul Amelina (Canadian Center of Science and Education, 2021)
In facing the Covid-19 pandemic, the teaching and learning landscape in Malaysian schools has also changed accordingly. The Ministry of Education has introduced Teaching and Learning at Home to take over the previous methods. Conventional teaching methods are unfitting during the ‘new norm’. Therefore, teachers need to diversify their instructional strategies and search for various resources in the digital environment - learning in this mode should create a fun digital learning environment. Digital Game-based Learning (DGBL) is a teaching aid that is capable of promoting enjoyment in learning. This article focused on DGBL as a learning method in a collaborative environment called Collaborative Game-based Learning (CGBL). There is a shortage of insight on the factors that support DGBL’s efficiency in the digital environment, specifically in CGBL in educational settings. This article employed a systematic Thematic Review (TR) approach to synthesise the literature published from 2016 until 2021 on CGBL in the digital environment. A keyword search was conducted, followed by a filtering process using inclusion criteria from the Scopus, Lens, and Mendeley databases. The author identified 65 peer-reviewed journal papers. Only 34 articles were used to be reviewed after the inclusion and exclusion processes. A TR of these articles identified 95 initial codes, later grouped into 32 codes, and created ten categories from three themes. From the TR results, it is found that the factors contributing to CGBL effectiveness are learning environment, learning motivation and learning strategies. This work provides insight on various parties in considering the implementation of CGBL in Teaching and Learning at Home as one of the appropriate alternative resources and methods.